Climate talks in Warsaw, Poland (COP19) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Led by Theme Long-term Adaptation, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) coordinated a side event on Agriculture in NAPs at the UNFCCC Conference of the Parties (COP19) in Warsaw, Poland. The side event reviewed the NAP process for climate change adaptation in the agriculture sector by synthesizing the experiences of 10 countries from Africa, Asia and Latin America, drawn from a 2-day workshop on NAPs and agriculture held in the days leading up to COP 19.